2020
DOI: 10.3892/ol.2020.11780
|View full text |Cite
|
Sign up to set email alerts
|

An optimal prognostic model based on gene expression for clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most prevalent type of RCC; however, prognostic prediction tools for ccRCC are scant. Developing mRNA or long non-coding RNA (lncRNA)-based risk assessment tools may improve the prognosis in patients with ccRCC. RNA-sequencing and prognostic data from patients with ccRCC were downloaded from The Cancer Genome Atlas and the European Bioinformatics Institute Array database at the National Center for Biotechnology Information. Differentially expressed (DE) RNAs (DERs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
6
1
Order By: Relevance
“…90 Similarly, 10 differentially expressed genes (AGR3, CSF2, GAL3ST2, IGLL1, PLG, SAA1, SBSN, SOX2, WFDC13, and ZIC2) were included in a recent prognostic risk assessment tool for ccRCC with AUC of 0.99 without a validation set. 91 The results from previous studies are not consistent with one from the current study. Potential reasons for inconsistency can be small sample sizes, different racial/ethnic background, potential environmental factors and more importantly, lack of validation set.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…90 Similarly, 10 differentially expressed genes (AGR3, CSF2, GAL3ST2, IGLL1, PLG, SAA1, SBSN, SOX2, WFDC13, and ZIC2) were included in a recent prognostic risk assessment tool for ccRCC with AUC of 0.99 without a validation set. 91 The results from previous studies are not consistent with one from the current study. Potential reasons for inconsistency can be small sample sizes, different racial/ethnic background, potential environmental factors and more importantly, lack of validation set.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, seven differentially expressed autophagy‐related genes ( PRKCQ , BID , BAG1 , BIRC5 , ATG16L2 , EIF4EBP1 , and ATG9B ) were included in a recent prognostic survival assessment tool for ccRCC with AUCs of 0.752 and 0.783 for overall and disease free survival, respectively 90 . Similarly, 10 differentially expressed genes ( AGR3 , CSF2 , GAL3ST2 , IGLL1 , PLG , SAA1 , SBSN , SOX2 , WFDC13 , and ZIC2 ) were included in a recent prognostic risk assessment tool for ccRCC with AUC of 0.99 without a validation set 91 . The results from previous studies are not consistent with one from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis and Cox regression analysis indicated that expression of IGFLR1 was a prognostic factor in ccRCC patients, rather than an independent prognostic factor (Sichani et al, 2010). Besides, although a number of previous studies have constructed prognostic risk models based on clinical factors, gene signature, or taking both into account (Chang et al, 2018;Chen et al, 2019Chen et al, , 2020Xu D. et al, 2020;Xu W.H. et al, 2020), IGFLR1 has not been reported as a factor in model construction.…”
Section: Discussionmentioning
confidence: 99%
“…Among five lncRNAs in the EpiLncRNASig, several lncRNAs have been well studied in some cancers. For example, LINC00189 has been reported to be associated with several cancers, including ovarian cancer, cervical cancer ( Zhang et al, 2020 ), clear cell renal cell carcinoma ( Xu et al, 2020 ), and urinary bladder cancer ( Zhang et al, 2016 ). By analyzing CACNA1G-AS1 expression levels in 122 pairs of non-small cell lung cancer (NSCLC) and normal tissue samples as well as in NSCLC cell lines, Yu et al (2018) identified CACNA1G-AS1 as an oncogene to promote cell migration, invasion, and epithelial-mesenchymal transition via regulating HNRNPA2B1 .…”
Section: Discussionmentioning
confidence: 99%